AKTIVITAS ENZIM HIDROLASE PADA PENAPISAN ISOLAT ACTINOMYCETES TOLERAN SALINITAS - Sumardi, Sumardi; Qatrunada, Vanya; Farisi, Salman; Arifiyanto, Achmad; Ekowati, Christina Nugroho; Farisi, Salman (Universitas Muhammadiyah Jember, 2021)
Actinomycetesis one of the microorganisms which have the ability of enzymes hydrolases such as cellulose, amylase, protease, and manannase. Manufacturer of enzymes of the hydrolase can be used as a candidate probiotic. A candidate probiotic should have a good resistance in different environmental conditions including pH and salinity.Â This research is conducted to filter the candidateâ€™s probiotics from bacteria Actinomycetes that tolerance salinity and has the activity of the enzyme hydrolase. Testing the activity of the enzyme was preformed qualitatively on the variation of pH 4, 7, and 9.8.Â Theability of Atinomycetesproduce enzymes hydrolases is indicated by the colony on media containing the substrate.From the test results, cellulase enzyme activity with the largest enzymatic index value is 3.5 AF2 isolates pH 9.8. Amylase enzyme activity with the largest enzymatic index value is 3.66 RH1 isolates pH 7. Protease enzyme activity with the largest enzyme index value is 0.66, AF2 isolates at pH 7. Mananase enzyme activity with the largest enzymatic index value is 0.85, namely AF2 isolates pH 4. In testing the effect of salinity test isolates were able to grow at variations in the concentration of NaCl 0, 3, and 6%.